The association Geranio phaei-Urticetum dioicae Hadač et al. (1969) in Central Pomerania - Sobisz, Zbigniew (Biodiversity: Research and Conservation, 2015)
Geranio phaei-Urticetum dioicae, a poorly known association of nitrophilous outskirts communities was characterized based on 16 phytosociological relevés. Its ecological requirements and distribution in Pomerania and Poland are presented. A new subassociations of the Geranio phaei-Urticetum dioicae allietosum ursini have been distinguished on the basis of differing species composition. Edaphic and phytocenotic conditions of the population were specified. Association is found in mineral soil of acid reaction abundant with nitrogen and phosphorus, and as to its quantity it belongs to less numerous ones at Pomerania.